2017
DOI: 10.1111/jpn.12812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Greek oregano (Origanum vulgare ssp. hirtum) supplementation on rumen fermentation, enzyme profile and microbial communities in goats

Abstract: This study was conducted to examine in vivo long-term effects of dietary dried oregano (Origanum vulgare ssp. hirtum) whole plant on rumen fermentation, enzyme profile and microbial communities. For this purpose, eight healthy, adult, non-lactating Alpine goats were kept in tie stalls equipped for individual feeding and randomly divided into two homogeneous groups: one fed 0.6 kg of a concentrate mixture and 0.6 kg of wheat straw without any supplementation and served as control group (CON) while the other gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
(41 reference statements)
3
3
0
2
Order By: Relevance
“…Our results support those of Hristov et al (2013), who did not observe changes in total VFA concentration, A:P ratio, or molar proportions of acetate and propionate. Furthermore, unaltered VFA molar proportions were reported previously (Wang et al, 2009;Tekippe et al, 2011;Kolling et al, 2018;Paraskevakis, 2018). The main effect of feeding low EO oregano on rumen fermentation was a decline in microbial CP synthesis in Exp.…”
Section: Apparent Nutrient Digestibility and Rumen Fermentationsupporting
confidence: 52%
“…Our results support those of Hristov et al (2013), who did not observe changes in total VFA concentration, A:P ratio, or molar proportions of acetate and propionate. Furthermore, unaltered VFA molar proportions were reported previously (Wang et al, 2009;Tekippe et al, 2011;Kolling et al, 2018;Paraskevakis, 2018). The main effect of feeding low EO oregano on rumen fermentation was a decline in microbial CP synthesis in Exp.…”
Section: Apparent Nutrient Digestibility and Rumen Fermentationsupporting
confidence: 52%
“…The results of ORO linearly reducing in vivo CH 4 emission supported our in vitro observations, especially to 20 and 40 ml/kg additive levels. This result was consistent with the research of Paraskevakis ( 2018 ), who found that 1 ml/day ORO suppressed specific rumen microorganisms in goats by inhibiting methanogens activity. Benchaar ( 2020 ) reported that 50 mg/kg DM of ORO had no effect on the total‐tract apparent nutrients digestibility and enteric CH 4 emission of dairy cow.…”
Section: Discussionsupporting
confidence: 93%
“…As the main constituents of ORO, carvacrol and thymol have similar chemical structures and are verified to have valid antimicrobial activities (Patra & Yu, 2015 ). The linear reduction of in vitro CH 4 and CO 2 emissions may be directly related to the specific inhibition by carvacrol and thymol on Prevotellaceae , Lachnospiraceae and Ruminococcaceae (Paraskevakis, 2018 ; Patra & Yu, 2015 ). In addition, the 40 mg/kg ORO significantly reduced CH 4 by 35.98%, and 20 and 40 mg/kg ORO significantly inhibited CO 2 by 46.16% and 55.85% compared to 0 mg/kg ORO, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in CH4 with the addition of OEO was consistent with the findings of others (Tekippe et al, 2011;Patra and Yu, 2012;Cobellis et al, 2015;Kolling et al, 2018) and could be attributed to the antimicrobial effects of the OEO on protozoa and methanogenic Archaea as reported by Patra and Yu (2012) and Paraskevakis (2018). Interestingly however, the reduction in CH4 was significant only when OEO was added to the adapted culture suggesting that microbial adaptation and/or modification played a role in OEO effect.…”
Section: Discussionsupporting
confidence: 89%